2022
DOI: 10.1111/febs.16386
|View full text |Cite
|
Sign up to set email alerts
|

Structural features determining the vitamin K epoxide reduction activity in the VKOR family of membrane oxidoreductases

Abstract: Vitamin K epoxide reductases (VKORs) are a large family of integral membrane enzymes found from bacteria to humans. Human VKOR, specific target of warfarin, has both the epoxide and quinone reductase activity to maintain the vitamin K cycle. Bacterial VKOR homologs, however, are insensitive to warfarin inhibition and are quinone reductases incapable of epoxide reduction. What affords the epoxide reductase activity in human VKOR remains unknown. Here, we show that a representative bacterial VKOR homolog can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…VK exists in two forms in nature: The first, called phylloquinone (also known as VK1), is found in photosynthetic organisms, such as green plants, cyanobacteria and algae; the other, namely menadione (also known as VK2), is found in animals and bacteria. VK is a redox-active naphthoquinone ( 71 , 72 ), which can be converted into its corresponding hydroquinone VKH2 and is found mainly in the mature VK cycle ( 61 , 73 ). Recently, Mishima et al ( 74 ) found that FSP1 reduces VK in the manner of ubiquitin ketone.…”
Section: Molecular Mechanism and Pathway Of Ferroptosismentioning
confidence: 99%
“…VK exists in two forms in nature: The first, called phylloquinone (also known as VK1), is found in photosynthetic organisms, such as green plants, cyanobacteria and algae; the other, namely menadione (also known as VK2), is found in animals and bacteria. VK is a redox-active naphthoquinone ( 71 , 72 ), which can be converted into its corresponding hydroquinone VKH2 and is found mainly in the mature VK cycle ( 61 , 73 ). Recently, Mishima et al ( 74 ) found that FSP1 reduces VK in the manner of ubiquitin ketone.…”
Section: Molecular Mechanism and Pathway Of Ferroptosismentioning
confidence: 99%
“…57,63,99,100 To clarify this issue, the SsVKOR homolog was converted to a warfarin-sensitive epoxide reductase (same as HsVKOR) with merely eight mutations and with addition of a membrane anchor domain. 101 This combination introduces the two key hydrogen bonds at the active site and changes the shape and flexibility of this pocket. These structural features largely determine…”
Section: Distinct Mechanisms Of Warfarin Resistancementioning
confidence: 99%
“…These key differences were taken also as evidence that HsVKOR and SsVKOR adopt completely different structural folds 57,63,99,100 . To clarify this issue, the SsVKOR homolog was converted to a warfarin‐sensitive epoxide reductase (same as HsVKOR) with merely eight mutations and with addition of a membrane anchor domain 101 . This combination introduces the two key hydrogen bonds at the active site and changes the shape and flexibility of this pocket.…”
Section: Warfarin Resistance Dosage and Antidotingmentioning
confidence: 99%
“…The 3D capillary model uses the relation between the pore size and pore number to determine the fractal dimension. The pore number N (> r ) with a pore radius larger than r can be obtained from the total mercury saturation V Hg ( r ) ,, where l is the core length. Figure a shows the process of fractal dimension calculation using the 3D capillary model, and the fractal dimension can be obtained from the slope of the log N (> r ) – log r curve in a log–log plot.…”
Section: Rate-controlled Porosimetrymentioning
confidence: 99%